Firenze per Claudio Magris - Pellegrini, Ernestina; Fastelli, Federico; Salvadori, Diego (Biblioteca di Studi di Filologia Moderna, 2021)
This volume brings together a selection of essays on Claudio Magris' work, aiming to enrich critical debate with a specific focus on interdisciplinary dimension and continuous dialogue with the main European literary traditions. The outcome is an overall study on Magris' narrative, essayistic and theatrical production, trying to fix his plural and prismatic identity: from the narration of places to an unavoidable ideological tension; from philosophical alphabets to the weight of History; from Myth's remediation to the abroad reception; from hypotext filigree to real case studies. According to a diachronic perspective, they focus attention on Magris' works, such as Microcosmi, Alla cieca, Non luogo a procedere and Tempo curvo a Krems.